GHG policy impacts for Seattle's buildings: targets, timing, and scope. Issue 1 (24th March 2021) - Walter, Travis; Mathew, Paul
Many US cities are addressing climate change by setting goals to reduce their greenhouse gas (GHG) emissions by a specified amount within a specified time period. In order to achieve these goals, reducing emissions from existing buildings is crucial. Many cities are passing legislation to target existing buildings through benchmarking, auditing, retuning, or energy or emissions performance standards. As cities design legislation, they must consider the timing of the policies, how to prioritize building types and sizes, and how these design decisions will impact the city's emissions. This paper addresses these questions for one particular US city: Seattle, Washington. A model of Seattle's building stock was created with benchmarking and tax assessor data. It was then used to predict GHG emissions reductions due to different policy implementations for existing commercial and multifamily buildings. Key findings are: (1) the proposed emissions policy is expected to reduce cumulative emissions from buildings by 19% between 2020 and 2050; (2) delaying the implementation of the policy by five years could limit savings to 12%; and (3) including smaller buildings in the policy could increase savings to 34%. The lessons learned and how this can be used by other cities are discussed. Practice relevance: As cities design legislation for energy performance standards, they must consider the impact that the timing of policies, prioritization of building types and sizes, and electrification will have on the city's GHG emissions. A new process is presented that can assist policymakers to understand the impacts of policy decisions on decarbonizing the building stock. A model of Seattle's building stock was created to predict emissions reductions due to different policy implementation scenarios. This model shows the impact of Seattle's proposed emissions policy. The current policy is expected to reduce cumulative emissions from buildings by 19% between 2020 and 2050. If the implementation of the policy is delayed by five years, then cumulative emissions savings would be reduced to 12%. The inclusion of smaller buildings in the policy could increase cumulative emissions savings to 34%. Other cities can use this process to better understand their proposed policies for their building stock.